Strategi Adaptasi Petani Perkotaan Melalui Pemanfaatan Media Hidroponik di Kota Semarang - Ivan Adidharma Riswandaputra; Nugroho Trisnu Brata (Yayasan Ekologi Masyarakat dan Sains, 2026)
The development of urban areas has led to an increasing limitation of agricultural land, thereby necessitating alternative strategies to sustain agricultural activities in cities. This study aims to analyze the utilization of hydroponic systems as a farming strategy adopted by urban farmers, as well as to examine the advantages, constraints, and socio-economic implications of implementing this method. The research employs a qualitative approach, using observation and in-depth interviews with hydroponic farmers who conduct commercial cultivation. The findings indicate that hydroponics is utilized as an adaptive strategy to address land scarcity, as it enhances spatial efficiency, increases the number of cultivated plants, and improves crop quality. Nevertheless, the implementation of hydroponic systems also faces several challenges, including relatively high initial investment costs, the need for meticulousness and consistency in maintenance, and consumer markets that differ from those of conventional agriculture. From a socio-economic perspective, hydroponic farming contributes to income stability among farmers and fosters new social relations and perspectives toward urban agriculture. Therefore, hydroponics holds significant potential as a sustainable urban farming strategy, provided that it is supported by improved knowledge, adequate infrastructure, and effective management.